2022
DOI: 10.1038/s41598-022-11116-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptors in breast cancer cells improves osteoblast viability in cancer-bone interaction model while reducing breast cancer cell survival and migration

Abstract: The endocannabinoid system has been postulated to help restrict cancer progression and maintain osteoblastic function during bone metastasis. Herein, the effects of cannabinoid receptor (CB) type 1 and 2 activation on breast cancer cell and osteoblast interaction were investigated by using ACEA and GW405833 as CB1 and CB2 agonists, respectively. Our results showed that breast cancer cell (MDA-MB-231)-derived conditioned media markedly decreased osteoblast-like UMR-106 cell viability. In contrast, media from MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Pharmacological activation or upregulation of CB1R and/or CB2R inhibits tumor growth and metastasis in vivo, attenuated proliferation, migration/invasion, and angiogenesis, and induced apoptosis in vitro through inhibition of extracellular signal-regulated kinase (ERK), protein kinase B (PKB)/AKT, cAMP/protein kinase A (PKA), c-Jun N-terminal kinase (JNK), MAPK p38, nuclear factor kappa B (NF-κB), and/or vascular endothelial growth factor (VEGF) signaling pathways, in various human cancers, including glioma [ 144 , 145 ], leukemia [ 146 , 147 , 148 ], multiple myeloma [ 149 ], neuroblastoma [ 150 ], breast [ 151 , 152 , 153 , 154 ], cervical [ 105 ], colorectal [ 110 , 155 , 156 , 157 ], endometrial [ 158 ], hepatocellular [ 159 ], intestinal [ 108 ], non-small-cell lung [ 160 , 161 ], prostate [ 162 , 163 ], and thyroid cancers [ 164 ]. The antitumorigenic and/or proapoptotic effects can be blocked by inhibition and/or knockdown of CB1R and/or CB2R [ 144 , 145 , 146 , 149 , 152 , 153 , 155 , 160 , 162 , 164 ].…”
Section: Ecs and Cancermentioning
confidence: 99%
“…Pharmacological activation or upregulation of CB1R and/or CB2R inhibits tumor growth and metastasis in vivo, attenuated proliferation, migration/invasion, and angiogenesis, and induced apoptosis in vitro through inhibition of extracellular signal-regulated kinase (ERK), protein kinase B (PKB)/AKT, cAMP/protein kinase A (PKA), c-Jun N-terminal kinase (JNK), MAPK p38, nuclear factor kappa B (NF-κB), and/or vascular endothelial growth factor (VEGF) signaling pathways, in various human cancers, including glioma [ 144 , 145 ], leukemia [ 146 , 147 , 148 ], multiple myeloma [ 149 ], neuroblastoma [ 150 ], breast [ 151 , 152 , 153 , 154 ], cervical [ 105 ], colorectal [ 110 , 155 , 156 , 157 ], endometrial [ 158 ], hepatocellular [ 159 ], intestinal [ 108 ], non-small-cell lung [ 160 , 161 ], prostate [ 162 , 163 ], and thyroid cancers [ 164 ]. The antitumorigenic and/or proapoptotic effects can be blocked by inhibition and/or knockdown of CB1R and/or CB2R [ 144 , 145 , 146 , 149 , 152 , 153 , 155 , 160 , 162 , 164 ].…”
Section: Ecs and Cancermentioning
confidence: 99%
“…Average percent cell viabilities are shown relative to control populations (Fig 1). TNBC cells have upregulated expression of the cannabinoid receptors CB1 and CB2 (Khunluck et al 2022). The susceptibility of TNBC cells to these agonists has only been recently appreciated.…”
Section: Resultsmentioning
confidence: 99%
“…It also found that JWH-133 and WIN-55,212-2 decreased tumor volume and angiogenesis in a group of mice that were subcutaneously injected with BC cell line, MDA-MB-231 cells. It also found that both JWH-133 and WIN-55,212 reduced lung metastasis (Khunluck et al 2022 ).…”
Section: Cannabis In Breast Cancermentioning
confidence: 97%
“…This leads to cell cycle arrest and subsequent apoptosis (Zhong et al 2023 ). Study found that cannabinoid receptor agonists, JWH-133 and WIN-55,212-2, decreased cell viability and migration in BC cell lines, MDA-MB-231, and MDA-MB-468 cell lines (Khunluck et al 2022 ). It also found that JWH-133 and WIN-55,212-2 decreased tumor volume and angiogenesis in a group of mice that were subcutaneously injected with BC cell line, MDA-MB-231 cells.…”
Section: Cannabis In Breast Cancermentioning
confidence: 99%